2017
DOI: 10.1001/jama.2016.10395
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Celiac Disease

Abstract: IMPORTANCE Silent or subclinical celiac disease may result in potentially avoidable adverse health consequences. OBJECTIVE To review the evidence on benefits and harms of screening for celiac disease in asymptomatic adults, adolescents, and children 3 years and older for the US Preventive Services Task Force. DATA SOURCES Ovid MEDLINE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews, searched to June 14, 2016. STUDY SELECTION Randomized clinical trials and cohort or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 43 publications
0
41
1
Order By: Relevance
“…According to our study, this approach can successfully exclude celiac disease in >99% of patients. Previous studies have shown that the sensitivity and specificity of anti‐TTG are 85–95% . While the sensitivity of anti‐TTG was only 80% in our study, this was likely due to a small sample size of patients with celiac disease and, therefore, increased variability of results.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…According to our study, this approach can successfully exclude celiac disease in >99% of patients. Previous studies have shown that the sensitivity and specificity of anti‐TTG are 85–95% . While the sensitivity of anti‐TTG was only 80% in our study, this was likely due to a small sample size of patients with celiac disease and, therefore, increased variability of results.…”
Section: Discussioncontrasting
confidence: 62%
“…There have also been advances made in serological screening and endoscopic imaging in the evaluation of celiac disease. In particular, with the use of antitissue transglutaminase antibody (anti‐TTG) and the assessment of total IgA levels (to exclude total IgA deficiency), celiac disease can be detected in up to 95% of patients . As a result, many guidelines suggested that negative serology may be sufficient to exclude celiac disease where the pretest probability is low .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of CD was high among autoimmune disease patients. The prevalence of CD varies among SLE patient groups; several reports showed a greater coexistence of CD among patients with SLE than among their matched controls [ 29 , 31 ]. There is similarity between the pathogenesis of CD and SLE, as both share a common genetic predilection favored by the presence of HLAB8 and HLA DR3 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Background : Gastroscopy is frequently performed for investigation of unexplained anemia, and small bowel biopsy (SBBx) is routinely recommended to exclude celiac disease. This approach may not be cost‐effective, given increasing evidence that celiac serology and advanced endoscopic imaging may be sufficiently sensitive to exclude celiac disease …”
Section: No Role For Routine Duodenal Biopsy In the Evaluation Of Patmentioning
confidence: 99%